1961
DOI: 10.1113/jphysiol.1961.sp006682
|View full text |Cite
|
Sign up to set email alerts
|

Chloride ions and the membrane potential of Purkinje fibres

Abstract: According to the ionic theory of electrical activity the membrane potential depends on the unequal distribution of ions between the intraand extracellular phases, and on the relative permeability of the membrane towards them. For cardiac muscle the role played by sodium and potassium has been studied to some extent (see Hoffman & Cranefield, 1960) but that of chloride has received little attention. The present paper deals with the effects produced by the substitution for chloride ions of nitrate ions or large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
82
2
2

Year Published

1965
1965
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(104 citation statements)
references
References 11 publications
18
82
2
2
Order By: Relevance
“…As a result, efflux of water from the inside of Purkinje cells may occur and decrease extracellular K+ concentration ([K+]0). It has been shown that both resting potential (Weidmann 1956) and K+ conductance during phase 4 (Carmeliet 1961) In summary, the data from the present experiment suggest that the mechanism for genesis of this VT may not be re-entry but rather enhanced automaticity.…”
Section: Discussionsupporting
confidence: 46%
“…As a result, efflux of water from the inside of Purkinje cells may occur and decrease extracellular K+ concentration ([K+]0). It has been shown that both resting potential (Weidmann 1956) and K+ conductance during phase 4 (Carmeliet 1961) In summary, the data from the present experiment suggest that the mechanism for genesis of this VT may not be re-entry but rather enhanced automaticity.…”
Section: Discussionsupporting
confidence: 46%
“…After a few minutes the membrane potential began to oscillate with a maximum amplitude of 30 mV and a cycle time of 0.5/sec to 1/sec (see also Carmeliet, 1961). Upon increasing the [Ca]0 the membrane hyperpolarized and the oscillations ceased.…”
Section: Effect Of Mn On the Ca Induced Decrease In Internal Namentioning
confidence: 93%
“…It was assumed that Cl-was in electrochemical equilibrium. According to Carmeliet (1960) this is not the case (at least in Purkinje fibres), and in depolarized cells Cl-currents may contribute significantly to membrane conductance. Until these possibilities can be directly investigated in the septum further speculation is not worthwhile.…”
Section: Discussionmentioning
confidence: 99%